Assessing the national seed production system of potato, shallot, and garlic. Issue 1 (November 2021) - Sayaka, B; Swastika, D K S; Sunarsih,
Abstract: A good seed production system results in quality seed. Subsequently, quality seed produces high yield, good quality, and uniform crop performance. This paper aims to assess the national vegetable seed system, especially those seeds produced using vegetative propagation, i.e. potato, shallot, and garlic. The study was conducted in 2019 in West Sumatera, West Java, Central Java, and Northern Sulawesi Provinces. Using primary data from the respondents and secondary data from related institutions, both data were analyzed descriptively. Indonesian Vegetable Research Institute (IVEGRI), universities, and seed companies produce various vegetable seeds. Community in groups or personals as well as regional governments may register their varieties to the Center for Crop Variety Protection and Agriculture Permit (PVTPP). Potato seed producers deal with higher production cost and the farmers have to pay more expensive seed since the Ministry of Agriculture (MoA) implemented the policy on shifting extension potato seed from G4 (fourth generation) to G2 (second generation). The farmers cope with quality and volume of garlic seed supply. Shallot seed adopted by the farmers are generally not certified. Farmers usually adopt certified shallot seed if they receive the government seed assistance. TSS (true shallot seed) has been introduced but farmers' adoption is limited. Garlic seed certification through post-harvest observation in the seed warehouse without field supervision was valid until the end of 2019 leading to low garlic yield. MoA should facilitate farmers with quality seed of improved vegetable varieties to enhance vegetable production as well as to improve farmers' profit.